Occurrence of aflatoxins contamination in brown rice from pakistan. - Muhammad Asif Asghar; Javed Iqbal; Aftab Ahmed; Mobeen Ahmed Khan (Tehran University of Medical Sciences, 2014)
The objective of this study was to determine the distribution of an economically-important class of mycotoxins, the aflatoxins (AFs) in Pakistani Brown Rice.A total of 262 of brown rice samples were collected from different vendors during July 2006 to June 2011. Samples were analyzed for the occurrence of aflatoxin B1 (AFB1), B2 (AFB2), G1 (AFG1) and G2 (AFG2) by thin layer chromatography (TLC) technique.AFB1 was detected in 250 (95.4%) samples, whereas AFB2 was detected in 20 (7.6%) samples. Furthermore, AFG1 and AFG2 were not found in any sample. The contamination range of AFB1 and AFB2 was found 1.07-24.65 μg/kg and 0.52-2.62 μg/kg, respectively. Total AFs were quantified in 250 (95.4%) samples with an average of 3.89 μg/kg and contamination range was noted to be between 1.07-27.27 μg/kg. The overall results indicated that in 12 (4.6%) samples, AFs were not found within detectable limits. Furthermore, in 188 (71.7%) samples, AFs level was found below than maximum tolerated levels (MTL) as recommended by the European Union (4 μg/kg). Moreover, in 61 (23.3%) samples, AFs range was found between 4-20 μg/kg, which were fit for human consumption as per MTL (20 μg/kg) assigned by USA (FDA and FAO) and Pakistan (PSQCA). While only one sample (27.27 μg/kg) exceeded the above mention regulation limits.Low level of AFs occurs frequently in brown rice, and can be improved using proper harvesting practices, storage and transportation conditions. The small quantities of AFs warrant performing further investigation, monitoring and routine analysis on regular basis.